Homogeneous focusing of electron bunch sequence by plasma wakefield - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Svistun, O.M. (Вопросы атомной науки и техники, 2012)
The mechanism of focusing of relativistic electron bunches by plasma wakefield, in which all bunches of sequence are focused identically and uniformly, has been proposed and investigated. In this scheme of focusing it is necessary that length of each bunch should be equal to a half of wavelength, the charge of first bunch equals half of the charge of the others bunches and the distance between bunches equals 1.5 of wavelength. It is shown that in this case only 1-st bunch is in the finite longitudinal electrical wakefield Ez. Other bunches are in zero longitudinal electrical wakefield Ez= 0. The focusing radial electrical field in regions, occupied by bunches, is constant along each bunch. Предложен и исследован механизм фокусировки релятивистских электронных сгустков плазменными кильватерными полями, в которых все сгустки последовательности фокусируются одинаково и однородно. В этой схеме фокусировки необходимо, чтобы длина каждого сгустка была равна половине длины кильватерной волны, заряд первого сгустка был в 2 раза меньше заряда каждого из остальных сгустков, а расстояние между ними составляло 1,5 длины волны. Показано, что в этом случае только на 1-й сгусток действует продольное поле Ez. Остальные сгустки находятся в нулевом продольном кильватерном поле Ez = 0. Фокусирующее радиальное поле в областях, занятых сгустками, постоянно по длине сгустков. Запропонований і досліджений механізм фокусування релятивістських електронних згустків плазмовими кільватерними полями, у яких усі згустки послідовності фокусуються однаково та однорідно. В цій схемі фокусування необхідно, щоб довжина кожного згустка дорівнювала половині довжини кільватерної хвилі, заряд першого згустку був у 2 рази менше заряда кожного із решти згустків, а відстань між ними була рівною 1,5 довжини хвилі. Показано, що в цьому випадку лише на 1-й згусток діє повздовжнє електричне поле Ez. Останні згустки знаходяться у нульовому повздовжньому кільватерному полі Ez = 0. Фокусуюче радіальне електричне поле в зонах, що заняті згустками, постійне по довжині згустків.